NCOG-03. PREDICTORS OF NEUROLOGIC DEATH IN PATIENTS WITH BRAIN METASTASES. (12th November 2021) - Reese, Alexander; Lamba, Nayan; Catalano, Paul; Cagney, Daniel; Wen, Patrick; Aizer, Ayal
Abstract: BACKGROUND: Neurologic death (ND), defined as intracranial disease progression with accompanying neurologic symptoms in the absence of life-threatening systemic disease, is the most serious consequence of intracranial disease among patients with brain metastases (BMs). Data indicating which factors are predictive of this outcome remain limited, however. Determining which patients are at increased risk of ND will guide improved care and further research aimed at preventing ND. METHODS: We identified 1, 218 patients with newly diagnosed BMs managed at Brigham and Women's Hospital from 2008-2015. Demographic and tumor characteristics for patients experiencing ND, non-neurologic death, and who were alive at last follow up were analyzed by univariable and multivariable Fine and Gray competing risks regression to identify predictors of ND, with non-neurologic death serving as a competing risk. RESULTS: In multivariable analysis, ND was associated with number of BMs (hazard ratio [HR] 1.01 per 1 metastasis increase, 95% CI 1.01-1.02, p< 0.001) and three primary tumor sites (with non-small cell lung cancer as the reference): melanoma (HR 4.67, 95% CI 3.27-6.68, p< 0.001), small cell lung cancer (HR 2.33, 95% CI 1.47-3.68, p< 0.001), and gastrointestinal cancer (HR 2.21, 95% CI 1.28-3.82, p=0.005). Additionally, among patients with breast primaries, HER2+ tumors displayed increased risk of ND relative to the reference subtype (HR+/HER2-) in univariable analysis (HR 2.41, 95% CI 1.00-5.84, p=0.05). A reduced risk of ND was found in patients with Karnofsky performance status of 90-100 versus 30-80 (HR 0.67, 95% CI 0.48-0.95, p=0.03) and progressive extracranial disease (HR 0.50, 95% CI 0.38-0.67, p< 0.001). CONCLUSION: Patients with melanoma, small cell lung cancer, gastrointestinal, and HER2+ breast cancer primaries, in addition to those with greater intracranial versus extracranial disease burdens, are at increased risk of ND. Future research into novel intracranial approaches should focus on these groups of patients.